Ornamental fish as a source of plasmid-mediated quinolone resistance genes and antibiotic resistance plasmids - Dobiasova, Hana; Kutilova, Iva; Piackova, Veronika; Vesely, Tomas; Cizek, Alois; Dolejska, Monika (Veterinary microbiology, 2014)
Growing ornamental fish industry is associated with public health concerns including extensive antibiotic use accompanied by increasing antibiotic resistance. The aim of this study was to analyze Aeromonas isolates from imported tropical ornamental fish and coldwater koi carps bred in the Czech Republic to assess the potential risk of ornamental fish as a source of plasmid-mediated quinolone resistance genes (PMQR) and antibiotic resistance plasmids. A collection of Aeromonas spp. with reduced susceptibility to ciprofloxacin (MIC ≥ 0.05 mg/L) was selected for the detection of PMQR genes. Isolates harbouring PMQR genes were further analyzed for the additional antibiotic resistance, integron content, clonality, biofilm production and transferability of PMQR genes by conjugation and transformation. Comparative analysis of plasmids carrying PMQR genes was performed. Fifteen (19%, n=80) isolates from koi carps and 18 (24%, n=76) isolates from imported ornamental fish were positive for qnrS2, aac(6')-Ib-cr or qnrB17 genes. PMQR-positive isolates from imported ornamental fish showed higher MIC levels to quinolones, multiresistance and diverse content of antibiotic resistance genes and integrons compared to the isolates from the carps. Related IncU plasmids harbouring qnrS2 and aac(6')-Ib-cr genes were found in Aeromonas spp. from imported ornamental fish and koi carps from various geographical areas. Ornamental fish may represent a potential source of multiresistant bacteria and mobile genetic elements for the environment and for humans.
Keywords: Animals; Base Sequence; Gram-Negative Bacterial Infections; mikrobiální testy citlivosti; polymerázová řetězová reakce; Polymerase Chain Reaction; kapři; nemoci ryb; lidé; Molecular Sequence Data; gramnegativní bakteriální infekce; Fish Diseases; Anti-Bacterial Agents; vodní hospodářství; DNA primery; Quinolone resistance; bakteriální léková rezistence; Aquaculture; ciprofloxacin; Blotting, Southern; Microbial Sensitivity Tests; molekulární sekvence - údaje; plazmidy; Ciprofloxacin; Ornamental fish; Czech Republic; sekvence nukleotidů; Carps; Sequence Analysis, DNA; Southernův blotting; Česká republika; DNA Primers; Plasmids; zvířata; sekvenční analýza DNA; antibakteriální látky; Aeromonas; Drug Resistance, Bacterial; Humans